On Generalized Continuous Fuzzy Proper Function from a Fuzzy Topological Space to another Fuzzy Topological Space (Baghdad Science Journal, 2019)
The purpose of this paper is to introduce and study the concepts of fuzzy generalized open sets, fuzzy generalized closed sets, generalized continuous fuzzy proper functions and prove results about these concepts.